The inhibition of human lung fibroblast proliferation and differentiation by Gs-coupled receptors is not predicted by the magnitude of cAMP response - Roberts, Maxine J.; Broome, Rebecca E.; Kent, Toby C.; Charlton, Steven J.; Rosethorne, Elizabeth M. (BioMed Central, 2018)
Background Idiopathic pulmonary fibrosis (IPF) is 22 a chronic and progressive fibrotic lung disease for which there is no cure. Current therapeutics are only able to slow disease progression, therefore there is a need to explore alternative, novel treatment options. There is increasing evidence that the 3’, 5’ cyclic adenosine monophosphate (cAMP) pathway is an important modulator in the development of fibrosis, with increasing levels of cAMP able to inhibit cellular processes associated with IPF. In this study we investigate the expression of Gs-coupled G protein-coupled receptors (GPCR) on human lung fibroblasts (HLF), and explore which can increase cAMP levels, and are most efficacious at inhibiting proliferation and differentiation. Methods Using TaqMan arrays we determined that fibroblasts express a range of Gs-coupled GPCR. The function of selected agonists at expressed receptors was then tested in a cAMP assay, and for their ability to inhibit fibroblast proliferation and differentiation. Results Expression analysis of GPCR showed that the prostacyclin, prostaglandin E2 (PGE2) receptor 2 and 4, melanocortin-1, β2 adrenoceptor, adenosine 2B, dopamine-1, and adenosine 2A receptors were expressed in HLF. Measuring cAMP accumulation in the presence of selected Gs-coupled receptor ligands as well as an adenylyl cyclase activator and inhibitors of phosphodiesterase showed formoterol, PGE2, treprostinil and forskolin elicited maximal cAMP responses. The agonists that fully inhibited both fibroblast proliferation and differentiation, BAY60-6583 and MRE-269, were partial agonists in the cAMP accumulation assay. Conclusions In this study we identified a number of ligands that act at a range of GPCR that increase cAMP and inhibit fibroblast proliferation and differentiation, suggesting that they may provide novel targets to develop new IPF treatments. From these results it appears that although the cAMP response is important in driving the anti-fibrotic effects we have observed, the magnitude of the acute cAMP response is not a good predictor of the extent of the inhibitory effect. This highlights the importance of monitoring the kinetics and localisation of intracellular signals, as well as multiple pathways when profiling novel compounds, as population second messenger assays may not always predict phenotypic outcomes.